Toxoids of Streptococcal Pyrogenic Exotoxin A Are Protective in Rabbit Models of Streptococcal Toxic Shock Syndrome - Roggiani, Manuela (American Society for Microbiology, 2000)
Streptococcal pyrogenic exotoxins (SPEs) are superantigens that have been implicated in causing streptococcal toxic shock syndrome (STSS). Most notably, SPE serotype A is made by nearly all M-protein serotype 1 and 3 streptococci, the M types most associated with the illness (these strains contain one or more other SPEs, and those proteins are likely also to contribute to disease). We have prepared double-, triple-, and hexa-amino-acid mutants of SPE A by PCR and other mutagenesis procedures. The sites chosen for mutation were solvent-exposed residues thought to be important for T-cell receptor (TCR) or major histocompatibility complex (MHC) class II interaction. These mutants were nonsuperantigenic for human peripheral blood mononuclear cells and rabbit and mouse splenocytes and were nonlethal in two rabbit models of STSS. In addition, these mutants stimulated protective antibody responses. Interestingly, mutants that altered toxin binding to MHC class II were more immunogenic than mutants altering TCR binding. Collectively, these studies indicate that multiple-site mutants of SPE A are toxoids that may have use in protecting against the toxin's effects in STSS.